In the jungle of time: the concept of identity as a way out - Zhou, Bin; Pöppel, Ernst; Bao, Yan (Frontiers in Psychology, 2014)
What could be a unifying principle for the manifold of temporal experiences: the simultaneity or temporal order of events, the subjective present, the duration of experiences, or the impression of a continuity of time? Furthermore, we time travel to the past visiting in imagination previous experiences in episodic memory, and we also time travel to the future anticipating actions or plans. For such time travelling we divide time into three domains: past, present, and future. What could be an escape out of this “jungle of time” characterized by many different perceptual and conceptual phenomena? The key concept we want to propose is “identity” which is derived from homeostasis as a fundamental biological principle. Within this conceptual frame two modes of identity are distinguished: Individual or self-identity required because of homeostatic demands, and object-related identity necessary for the reliability and efficiency of neuro-cognitive processing. With this concept of self- and object-identity, the different temporal experiences can be conceptualized within a common frame. Thus, we propose a fundamental biological principle to conceptually unify temporal phenomena on the psychological level.